The Use of Artificial Intelligence (AI) in Learning Results for Scientific Indonesian Language Courses at PGRI Wiranegara University - Sugianti; Rosidah, Ilmiyatur (MultiTech Publisher, 2024)
This research explores the impact of using Artificial Intelligence (AI) on scientific Indonesian language learning outcomes at PGRI Wiranegara University. With quantitative and qualitative approaches, this research shows a significant increase in the academic achievement of students who receive AI-based learning. The results of the analysis show a positive difference in values between the experimental group and the control group. Students reported positive experiences regarding AI assistance in overcoming learning difficulties. The conclusion confirms that AI integration is effective in improving the efficiency and quality of scientific Indonesian language learning in higher education. This research contributes to the development of innovative learning methods based on AI technology in higher education environments.